Eclips Props to Probe Motivation of Visual Impairment Students in Learning Science (Journal of Primary Education, 2019)
The purpose of this research was to describe the Special Needs School (SNS) students’ learning motivation improvement by using props. The research design used is one group pretest-posttest design. Data collecting techniques used are questionnaires and interview. The research subjects were four students with visual impairment in SNS ABC Swadaya Kendal. Two students suffer from low vision and two others suffer from total blindness. The data analysis used is percentage descriptive. This research was conducted for three meetings. The learning model used was inquiry model with eclipse as the material. The result of students’ motivation improvement was up to 25 %. The motivation of SNS students can be improved with the help of eclipse props especially in science lesson.